Consulta previa como garantía de la sostenibilidad ambiental y la participación efectiva de las comunidades (Tema Central) - Angulo Villacís, Víctor Manuel (2026)
This study delves into the right to free, prior, and informed consultation, as established in the Constitution of the Republic of Ecuador. It also examines its role as a key mechanism for ensuring environmental sustainability and the active participation of Indigenous communities. Importantly, this right differs from environmental consultation, which focuses on broader citizen participation, thus avoiding the conceptual confusions often found in legal literature. Using a qualitative and documentary approach, the research reviews national legislation, Constitutional Court jurisprudence, and landmark extractive cases such as Yasuní-ITT and the Mirador mining project. The analysis incorporates an intercultural perspective that recognizes the distinctive forms of deliberation and organization within Indigenous peoples and connects prior consultation to current debates on climate justice and sustainable development. The findings reveal that, although the legal framework is robust, its implementation remains limited and largely dependent on political will. In conclusion, strengthening prior consultation as a binding and transparent instrument is essential to harmonize collective rights, environmental protection, and the country’s sustainability goals.